Pengaruh Bauran Pemasaran dan Destination Image Terhadap Keputusan Wisatawan Berkunjung Pada Pada Pariwisata Syariah Di Kabupaten Lima Puluh Kota Provinsi Sumatera Barat - Muhammad Yusuf (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2020)
The purpose of this study is to determine whether there is a partially and simultaneously influence among product, promotion, place, price, people, physical evidence, process, promise, patience and destination image variable on the decision of tourists visiting sharia tourism in Lima Puluh Regency, West Sumatra Province. This research is field research with quantitative research methods. The data collecting techniques of this study were questionnaire, documentation, and interviews with the respondents, which consist of 100 people. The research location of this study was in Lima Puluh Kota. In processing data, this study utilized SPSS for Windows program 23.0 version.Based on the research results, it is obtained that (1) marketing mix consisting of variables (product, price, place, promotion, people, process, physical evidence, promise, patience) has a positive influence on the decision of tourists visiting sharia tourism, , (2) destination image has a positive influence on the decision of tourists visiting sharia tourism, the marketing mix and destination image simultaneously influence the decision of visiting tourists by 44,019. It means that the product, price, place, promotion, people, process, physical evidence, promise, patience, and destination image variable simultaneously influence the decision of tourists visiting sharia tourism in the Lima Puluh regency of West Sumatra Province. Keywords: Sharia Marketing Mix, Destination Image, and Tourist Visit Decision, Sharia Tourism